The achilles- heel of doctoral education in African higher education institutions: an Ethiopian university in perspective. Issue 4 (7th June 2022) - Tamrat, Wondwosen; Fetene, Getnet Tizazu
ABSTRACT: This study explores doctoral students' views about the support schemes and resources deployed to run PhD programs at one public university in Ethiopia. The research used questionnaire, interview and documentary evidence as principal data collection tools and involved 164 doctoral students at four purposely selected colleges of the university. The findings reveal that the human resource, facilities, support systems, financial assistance, climate (working environment), workshop and conference opportunities, provision of special trainings, and opportunities for publication of research papers are rated by doctoral candidates as highly deficient across all the four colleges. The findings of the study further indicate that the provisions of doctoral education at the sample university is far below the demands of PhD students for a diverse scheme of support which is regarded as critical to the quality of training they receive and the timely completion of their studies. It is argued that the provision of PhD programs will continue to be seriously hampered unless a significant improvement is made in terms of overhauling both the national direction set and the support mechanisms put in place.